Optimal extent of lymphadenectomy for radical surgery of pancreatic head adenocarcinoma: 2-year survival rate results of single-center, prospective, randomized controlled study. Issue 35 (3rd September 2021) - Wang, Ziyao; Ke, Nengwen; Wang, Xin; Wang, Xing; Chen, Yonghua; Chen, Hongyu; Liu, Jinheng; He, Du; Tian, Bole; Li, Ang; Hu, Weiming; Li, Kezhou; et al.
Abstract: Background: Radical pancreaticoduodenectomy is the only possible cure for pancreatic head adenocarcinoma, and although several RCT studies have suggested the extent of lymph node dissection, this issue remains controversial. This article wanted to evaluate the survival benefit of different lymph node dissection extent for radical surgical treatment of pancreatic head adenocarcinoma. Methods: A total of 240 patients were assessed for eligibility in the study, 212 of whom were randomly divided into standard lymphadenectomy group (SG) or extended lymphadenectomy group (EG), there were 97 patients in SG and 95 patients in EG receiving the radical pancreaticoduodenectomy. Result: The demography, histopathology and clinical characteristics were similar between the 2 groups. The 2-year overall survival rate in the SG was higher than the EG (39.5% vs 25.3%; P  = .034). The 2-year overall survival rate in the SG who received postoperative adjuvant chemotherapy was higher than the EG (60.7% vs 37.1%; P  = .021). There was no significant difference in the overall incidence of complications between the 2 groups ( P  = .502). The overall recurrence rate in the SG and EG (70.7% vs 77.5%; P  = .349), and the patterns of recurrence between 2 groups were no significant differences. Conclusion: In multimodality therapy system, the efficacy of chemotherapy should be based on the appropriate lymphadenectomy extent, and the standard extent of lymphadenectomy is optimal for resectable pancreatic head adenocarcinoma. The postoperative slowing of peripheral blood lymphocyte recovery might be 1 of the reasons why extended lymphadenectomy did not result in survival benefits. Clinical trial registration: This trial was registered at ClinicalTrials.gov (NCT02928081) in October 7, 2016. https://clinicaltrials.gov/ Abstract : Supplemental Digital Content is available in the text